Implementación de un Sistema de Gestión Socio-Ambiental para la Asociación de Desarrollo Agropecuario “La Esmeralda” parroquia la Esmeralda, cantón Montalvo, Provincia de Los Ríos - Lopez Haro, Alex Alonso (2017)
SUMMARY The System of Management Environmental Partner, there executed in the Association of Agricultural Development "La Esmeralda" located in the parish La Esmeralda of the Montalvo city. As a general objetive for the production of the project was Environmental Partner formulated the implementation of a system of Management, in that there was designed an Action plan and Program of Training directed all the members of the estate, giving the policies of the Procedure RAS and in her the Program of Health and Occupational Security, The Plan of Managing waste, and the Social and Environmental System. The applied methodology was based on three phases of management of the Network of Sustainable Agriculture (RAS). The diagnoses of agreement realized to the impositions of the Procedure RAS, with the help of the members of the Association the general audit of the estate was executed. All the workers were qualified and informed the benefits that are acquired on having requested Rainforest Alliance's certification. Thanks to the complete acceptance the project executed with facility, demonstrating the sustainability in the corners of the Association, keeping the Environmental Partner supporting the program in this estate, developing and respecting the policies of the Procedure in order not to lose the Certification.